New evidence of putative Unenlagiinae (Deinonychosauria, Theropoda) in the São Luís-Grajaú Basin, Albian– Cenomanian, State of Maranhão, Brazil. - Letizio, Luiz Antonio [UNESP] (2022)
We studied an assemblage of teeth from Laje do Coringa, São Luís-Grajaú Basin, Alcântara Formation, State of Maranhão, Brazil. The collection sites are dated as Albian–Cenomanian. Ten teeth were submitted to morphological analysis in Scanning Electron Microscopy, with the goal of identifying materials likely associated with unenlagiine theropod dinosaurs. Three specimens were identified as putative members of the group based on: (a) strong labial-lingual flattening of the crown, (b) absence of longitudinal grooves, (c) dimensions compatible with previously described Unenlagiinae, (d) “ziphodont” morphology lightly to the mesial portion, (e) basal section with two distinguishable borders, (f) complete absence of serrations. These teeth expand chronological and geographical distributions of Unenlagiinae dinosaurs.